The ideas of social justice and basic human rights in the socio-political discourse of Armenia - Mkrtchyan, Naira (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
The article examines issues concerning the agenda of deep changes, its ideological frame after the collapse of th USSR, in this context particulalrly the relating and articulation of social justice and basic human rights as primary values in the public political discourse in Armenia recently.
Keywords: սոցիալական արդարություն; մարդու հիմնարար իրավունքներ; հանրային-քաղաքական խոսույթ; խորքային փոփոխություններ; հասարակական-պետական կերտվածք; գաղափարաբանական շրջանակ; ազատական ժողովրդավարություն; համակարգային բարեփոխումների օրակարգ